Kepastian Hukum Bagi Investor Asing di Indonesia: Analisa Hukum Berdasarkan Undang-Undang Nomor 25 Tahun 2007 Tentang Penanaman Modal - Prayudha, Eko Irianto (SENTRI: Jurnal Riset Ilmiah, 2025)
In domestic economic development, the Government of Indonesia opens opportunities for investors, both domestic and foreign, to participate in strategic projects, through investment. Regarding Investment from Foreign Investors, Indonesia acts as a Host State or Capital Recipient State to regulate the "rules of the game" for capital management through Law Number 25 of 2007 concerning Investment. In the midst of uncertain economic, political and legal conditions, of course it makes foreign investors "think twice" to invest in Indonesia, considering the situation of Economic, Political and Legal conditions greatly affecting the investment climate in Indonesia. Furthermore, it is important to provide legal certainty and provide a sense of comfort to Foreign Investors, the Government of Indonesia issued Law Number 25 of 2007 concerning Investment, which regulates the management of Investment in Indonesia, the basic policies of Investment, the Form of Business Entity, the Business Sector, Investment Development, Investment Facilities, Licensing, as well as the Rights, Obligations and Responsibilities of Investors as well as Dispute Resolution.